California manual of temporary traffic control : 2012 field guide for temporary traffic control : for construction and maintenance work zones (BNI Building News, 2012)
As of January 13, 2012, the California Department of Transportation replaced the Caltrans Traffic Manual with a 2012 California Manual of Uniform Traffic Control Devices. Part 6 of the 2012 MUTCD covers temporary Traffic Controls, and now BNi Building News has assembled all of the essential figures and illustrations from part 6 into a convenient, pocket-sized guide that can be easily referenced on the jobsite. Without having to carry a 320-page manual on the jobsite, you can have full access to the temporary traffic control graphics from the California MUTCD anywhere you go.